Identifikasi Penerapan Solar Panel pada Redesain Pesantren Darul Istiqamah Timbuseng di Kabupaten Gowa - Gufron, Ahmad; Marwati, Marwati; Amin, Burhanuddin (TIMPALAJA : Architecture Student Journals, 2021)
Abstract_Pondok Pesantren is very important for every human being from children to adults, both formally and informally. Pondok Pesantren is basically a place for students to learn. Therefore, the Darul Istiqamah Timbuseng Islamic Boarding School in Gowa Regency is an alternative, especially for those who want to study general education and religious education. The location of the Darul Istiqamah Islamic Boarding School Timbuseng is on Jalan Institution, Pattallassang District, Gowa Regency. The use of solar panels is an alternative that can be used in the redesign concept of Islamic boarding schools. This study aims to identify the solar panel system used in the redesign of the pesantren. The data obtained from the results of the exploration of the design of the pesantren were then analyzed descriptively and qualitatively. The application of solar panels with a PV system in buildings with a saddle/shield form dominates on the roof of the building.